The influence of christian democratic trend in the EU integration process - Gönültaş, Zeynep Hazal (My University, 2009)
Bu yüksek lisans çalışmasının amacı, Hristiyan Demokratların Avrupa Birliği bütünleşme sürecindeki etkinlerinin araştırılmasıdır. Hristiyan Demokrat akımının Avrupa Birliği’nin oluşum sürecinde etkilerinin olup olmadığı, etkileri olduysa bunların ne yönde ve ne derecede etkili olduğu, tarihsel süreç takip edilerek, neden sonuç ilişkisi içinde incelenmiştir. Son olarak ise Hristiyan Demokrat parti, European People’s Party’nin Türkiye üyeliğine bakış açısı ele alınmıştır. Bu amaçla ilk bölümde Hristiyan Demokrat akımın Avrupa’da ortaya çıkışı ve zaman içinde geçirdiği dönüşümler incelenmiştir. Özellikle ortaya çıkışları, kimliksel dönüşümleri ve uluslarüstü özellikleri üzerinde durulmuştur. İkinci bölümde ise Hristiyan Demokratların AB’nin bütünleşmesinin ilk adımlarındaki etkileri incelenmiştir. Üçüncü ve son bölümde ise Avrupa Birliği’nin yapısı ve gelişimini temelden etkileyen anlaşmakardaki, etkileri üzerinde durulmuştur.

The main objective of this thesis is the exploration of the influence of Christian Democrats on the EU integration process. This research approaches in a historical context and analyses in a causal relationship the question whether the Christian Democrats as a political movement have been influential in the formation of the European Union, and if they have to what extent this influence has been effective. As a final point, it also dwells on the issue of how the Christian Democrats, European People’s Party, evaluates Turkey’s possible membership to the European Union. With this objectives in mind, the first chapter of this study focuses on the emergence of the Christian Democrats as political movement in Europe, and traces the transformation that it went through during its historical development. It especially dwells on the transformation of the movement’s political identity and its supranational quality. The second chapter is concerned with the influence of the Christian Democrats on the initial steps of the EU integration. The third and the last chapter, on the other hand, covers their involvement in the treaties that determined the structure and development of the EU.
Keywords: Avrupa Birliği; Hristiyanlık_Demokrasi; Siyaset ve Yönetim; Uluslararası İlişkiler